Dynamic Cervical Implant versus Anterior Cervical Diskectomy and Fusion: A Prospective Study of Clinical and Radiologic Outcome - Richter, Heiko; Seule, Martin; Hildebrandt, Gerhard; Fournier, Jean-Yves (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective To evaluate clinical and radiologic outcome in patients treated with a dynamic cervical implant (DCI) or anterior cervical diskectomy and fusion (ACDF).Study Design A prospective comparative cohort study.Methods The study included 60 patients with one- or two-level cervical degenerative disk disease (DDD) undergoing treatment with either DCI (n = 30) or ACDF (n = 30). Clinical and radiologic outcomes were assessed 3 and 12 months after surgery. Clinical scoring systems included the Visual Analog Scale for Neck (VAS-N) and Arm pain (VAS-A), the Neck Pain and Disability Scale (NPAD), and the European Quality of Life Scale (EQ-5D).Results Both the DCI and ACDF group showed significant clinical improvement 12 months after surgery using the VAS-N (p = 0.034 and p < 0.001, respectively), VAS-A (p < 0.001 and p < 0.001, respectively), NPAD (p < 0.001 and p < 0.001, respectively), and EQ-5D (p < 0.001 and p < 0.001, respectively). There were no significant differences in clinical outcome comparing both groups at the 3- and 12-month follow-up. The fusion rate at 12 months after surgery was 39.4% and 80.0% in the DCI and ACDF groups, respectively. Radiolucency was found in 90.9% in the DCI group at 12-month follow-up.Conclusion The clinical results for DCI treatment are equivalent to those for ACDF in the treatment of one- and two-level cervical DDD at 12 months after surgery. Further studies are necessary to investigate the high rates of radiolucency and fusion associated with DCI treatment.
Keywords: dynamic cervical implant; anterior cervical diskectomy and fusion; cervical spine; adjacent segment disease; cervical disk arthroplasty